"Investigating the differences between steel slag and natural limestone in asphalt mixes in terms of microscopic mechanism, fatigue behavior and microwave-induced healing performance". (18th April 2022) - Wang, Riran; Xiong, Yuchao; Ma, Xiaopeng; Guo, Yajun; Yue, Mingjing; Yue, Jinchao
Graphical abstract: Highlights: Microscopic characterization indicated that steel slag is porous and includes iron-containing microwave-absorbing components. 70-SS mastic has better crystallization and superior thermal stability than those of 70-LS mastic. The microwave absorption and heating rate of the steel slag asphalt mastic are promoted by its magnetic components. Fatigue resistance and healing capacity under microwave radiation of steel slag FAM were better than those of limestone FAM. The microwave-induced healing efficiency of steel slag FAM was obviously greater than that under self-healing mechanism. Abstract: Reducing the consumption of non-renewable aggregate and replacing it with steel slag waste is one of the feasible measures to produce cleaner asphalt pavement, which is conducive to the sustainable development of transportation infrastructure. This investigation was to assess the differentiation between steel slag and natural limestone in asphalt mastic and fine aggregate matrix (FAM) from perspectives of microscopic characteristics of raw materials, fatigue behavior and microwave induced healing capacity. First, differences in the characteristics of steel slag and limestone fillers and the microscopic interactions between fillers and bitumen were evaluated by scanning electron microscope, X-ray diffraction, X-ray photoelectron spectroscopy, thermo gravimetric analyzer, and Fourier transform infrared spectroscopy. Second, the fatigue behavior and microwave heating capability of steel slag asphalt mastic (70-SS) and limestone asphalt mastic (70-LS) were performed on dynamic shear rhemeter device and microwave generator in a laboratory. Third, the fatigue life of steel slag FAM (SS-FAM) and limestone FAM (LS-FAM) were predicted under the framework of viscoelastic continuum damage (VECD) model, and performance of FAM mixes under microwave-induced healing (MIH) and self-healing (SH) mechanisms was also analyzed. Furthermore, a comprehensive statistical analysis was accomplished by radar plots from micro- and macro-view. Microscopic characterization indicates that steel slag is porous and contains microwave-absorbing components, and reveals that 70-SS has better crystallization and superior thermal stability than 70-LS. The fatigue life of unaged 70-LS is greater than that of 70-SS and vice versa for aged specimen. The microwave absorption and heating rate of 70-SS are promoted by its magnetic components. Fatigue resistance and healing capacity under microwave radiation of SS-FAM are better than those of LS-FAM, and MIH efficiency is obviously greater than that under SH mechanism. Statistical outcomes demonstrates that the performance ranking of the mastic system is in agreement with that of the corresponding FAM system.